Table of tractates in the Coptic Gnostic Library (TOTITCGL_I_XXII) - Attridge, Harold W. (BrillOnline Reference Works, 2012)
The following table lists, for the thirteen Nag Hammadi Codices and Papyrus Berolinensis 8502, the codex and tractate numbers, the tractate titles as used in this edition (the titles found in the tractates themselves, sometimes simplified and standardized, or, when the tractate bears no surviving title, one supplied by the editors), and the abbreviations of these titles